(untitled) (Global Journal of Management and Business Research, 2018)
This study is related to the human resource management practices of Arcadia group United Kingdom (UK). This is descriptive in nature that covers the area of the human resource practices part of the organization. Human resource manager plays a crucial role in the screening of human resource management and finds a strategically fit resource for the organization. The Arcadia Group#x2019;s line management focuses on the integration inconsistent with the personnel management system of global orientation human resource management and adjustment of keeping a pace of abilities. Recruitment system, planning growth of human resource implementation policy, legislation issues, and motivation criteria make the organization exceptionally different than the other organization strategically. The judgment of the recruitment system of Arcadia Group has been integrated with a set of actions to assist the logical steps of employing in an efficient adjustment nature. Proper communication and reward management system of this company is basically a channel of human resource management practices that adopt the database and customer relationship management system. It has been observed that the organization doing differently in strategically than the previous judgment in technical term of business development that means right people in right place through impacting the mechanism.